KAJIAN TENTANG NILAI-NILAI KARAKTER DALAM PEMBELAJARAN BAHASA INGGRIS JURUSAN IPS TINGKAT SMAN DI KOTA BANJARMASIN - Moh Yamin; Wahyu wahyu; Mariatul Kiptiah (Scientia: Jurnal Hasil Penelitian, 2016)
this research aims to find out the appropriate material and character values that should be insertted in teaching English to high school students majoring in social studies in Banjarmasin. The method used is a qualitative descriptive intended to describe the material and values through English. The results showed that the text that can be used in learning the English language-based character education cover the text on character; one's experience; history and stories about everyday life; text about history and everyday life; text about the social, religious, economic, cultural and others; text about the warriors of the nation and world leaders; the story of the cunning hare and the crocodile; text about social life and history; text on ethics and the importance of implementing in their daily lives; text that contains a positive value for the students; the story of the good trustee; text about student's discipline, caring and sharing; text on myth and legend; local stories; funny stories that educate and contains a mandate for good daily; text about the self development for interaction; and text about lessons of life.